1984
DOI: 10.1901/jaba.1984.17-23
|View full text |Cite
|
Sign up to set email alerts
|

Prompting and Stimulus Shaping Procedures for Teaching Visual‐motor Skills to Retarded Children

Abstract: Stimulus shaping appears to be a highly successful way to teach discrimination skills. In stimulus shaping, the topographical configuration of the stimuli is gradually changed over trials so that discrimination is at first easy, and then gradually more difficult. Stimulus shaping procedures might also be effective for training visual-motor tasks. Two experiments were conducted to assess the relative effectiveness of stimulus shaping and "traditional" prompting procedures. Pegboard skills were trained in Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 17 publications
(25 reference statements)
2
16
1
Order By: Relevance
“…Perhaps this blocking effect is so strong that techniques such as fading are not powerful enough to overcome the problem. Perhaps fading procedures are indeed unable to completely or efficiently divert the children's attention to the critical elements (Walsh & Lamberts, 1979;Mosk & Bucher, 1984). In fact, literature on compound learning with animal subjects has indicated that, given a previously established association between a stimulus and a response, an added element cannot fully divert attention on to itself and thus response acquisition to the added element will be impaired to some degree (Kehoe, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this blocking effect is so strong that techniques such as fading are not powerful enough to overcome the problem. Perhaps fading procedures are indeed unable to completely or efficiently divert the children's attention to the critical elements (Walsh & Lamberts, 1979;Mosk & Bucher, 1984). In fact, literature on compound learning with animal subjects has indicated that, given a previously established association between a stimulus and a response, an added element cannot fully divert attention on to itself and thus response acquisition to the added element will be impaired to some degree (Kehoe, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…For example, procedures involving systematic shaping or fading of stimulus characteristics have allowed more complex discriminations to be taught to persons with mental retardation (e.g., Mosk & Bucher, 1984). Likewise, well-documented procedures for prompting responses, then fading prompts as student performance improves, have demonstrated efficacy in the instruction of such self-help skills as toothbrushing (Horner & Keilitz, 1975), dressing (Azrin, Schaeffer, & Wesolowki, 1976), toileting (Foxx & Azrin, 1973), and eating (Azrin & Armstrong, 1973).…”
Section: An Examination Of Two Prompt Fadingmentioning
confidence: 99%
“…These results extend previous findings on prompting strategies by focusing on the acquisition of complex behaviors by severely handicapped learners. Although various authors have compared the effectiveness of prompting strategies with discrete behaviors (e.g., Mosk & Bucher, 1984), our study compared two instructional prompt strategies with complex behavior that were both functional and age appropriate.…”
Section: Resultsmentioning
confidence: 99%